2020
DOI: 10.3390/jcm9051370
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients with Clinical Stage I-IIIA Large-Cell Neuroendocrine Lung Cancer Treated with Resection

Abstract: Large-cell neuroendocrine carcinoma (LCNEC) is a rare malignancy with poor prognosis. The rationale of the study was to determine the survival of LCNEC patients in I–IIIA clinical stages who underwent resection. A total of 53 LCNEC (89%) and combined LCNEC (11%) patients in stages I–IIIA who underwent surgery with radical intent between 2002–2018 were included in the current study. Overall survival (OS) and time to recurrence (TTR) were estimated. Uni- and multivariable analyses were conducted using Cox-regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Another large retrospective study from Gu et al showed that surgery, when feasible, significantly and independently improved OS compared to a cohort of not surgically treated patients (adjusted with propensity score matching-PSMmethod); this was demonstrated for stages I-II (p = 0.000), for stage IIIA (p = 0.001), and even for stage IIIB (p = 0.017), although the high recurrence rate after surgery alone justifies the need for a multimodal treatment in all-stage LCNEC (55). Several smaller series are in line with the above-mentioned studies, as demonstrated by Girelli et al ( 56), Lowczak et al (57), and Zacharias et al (58). The latter study also demonstrated a possible role for systematic mediastinal nodal dissection in improving outcomes in LCNEC, but this finding might be explained by a more accurate staging of the disease.…”
Section: Early Stage: Role Of Surgery and Radiotherapysupporting
confidence: 72%
“…Another large retrospective study from Gu et al showed that surgery, when feasible, significantly and independently improved OS compared to a cohort of not surgically treated patients (adjusted with propensity score matching-PSMmethod); this was demonstrated for stages I-II (p = 0.000), for stage IIIA (p = 0.001), and even for stage IIIB (p = 0.017), although the high recurrence rate after surgery alone justifies the need for a multimodal treatment in all-stage LCNEC (55). Several smaller series are in line with the above-mentioned studies, as demonstrated by Girelli et al ( 56), Lowczak et al (57), and Zacharias et al (58). The latter study also demonstrated a possible role for systematic mediastinal nodal dissection in improving outcomes in LCNEC, but this finding might be explained by a more accurate staging of the disease.…”
Section: Early Stage: Role Of Surgery and Radiotherapysupporting
confidence: 72%
“…However, a clear prognostic value for the type of surgery in early-stage LCNEC has not been elucidated. Some evidence supports that a less radical surgery significantly increased the clinical outcome [ 7 , 34 ]. On the contrary, other works report better outcomes for patients who received lobectomy compared to the ones that received sub-lobar resections [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we identified a relevant role for patient age, with older patients having a significantly higher risk of tumor recurrence and death. A previous analysis detected age (≤64 vs. >64 years) as an independent factor influencing OS for LCNEC patients, with an increased risk of death in older patients, twice as higher compared to younger patients [ 34 ]. Recently, a nomogram model has been developed to predict the survival probability of LCNEC patients [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…( 10 ) However, LCNEC had a high postoperative recurrence rate, with more than half relapsing within one year, although the R0 resection margin and N0 status (no lymph node metastasis) improved the time to recurrence. ( 33 ) As a result, even for LCNEC patients with an earlier stage, surgery alone was insufficient. ( 34 ) Second, chemotherapy alone could be more beneficial than other treatments, even for patients in stage IV.…”
Section: Discussionmentioning
confidence: 99%